A study of the functional domains of the type I iterative polyketide synthase CalE8 in calicheamicin biosynthesis. - Elavazhagan Murugan. (2013)
Naturally occurring enediynes are potent antibiotics produced by soil and marine microorganisms. Their robust antitumor activities and unique mode of action make them a significant topic of study. The synthesis of the enediyne products is initiated by a type I iterative polyketide synthase (PKS). In this project, we examine the structures and functions of the domains of CalE8, to demarcate the domains of the the iterative PKS from the biosynthetic pathway of the 10-membered enediyne calicheamicin in Micromonospora echinospora spp.